Orofacial Myofunctional Therapy: Investigating a Novel Therapeutic Approach for Pediatric Obstructive Sleep Apnea in Children with and Without Down Syndrome—A Study Protocol - Jolien Verbeke; Iris Meerschman; Karlien Dhondt; Els De Leenheer; Julie Willekens; Kristiane Van Lierde; Sofie Claeys (Children)
Background/Objectives: Pediatric obstructive sleep apnea (OSA) is a prevalent medical condition, affecting 1–5% of non-syndromic children and 30–90% of children with Down syndrome. Given the severity of the condition and the associated health risks, early and effective treatment is crucial. However, current treatment modalities are often invasive or suffer from poor patient adherence. Additionally, adenotonsillectomy, the first-line treatment in pediatric OSA, seems not to be effective in every child, leaving children with residual OSA postoperatively. These challenges are particularly pronounced in high-risk populations, such as children with Down syndrome, highlighting the need for alternative therapeutic strategies. Therefore, a protocol is presented to evaluate the effectiveness of orofacial myofunctional therapy (OMT) as a treatment for OSA in two pediatric populations: (1) Non-syndromic children aged 4–18 years: 10 weeks of OMT. (2) Children with Down syndrome aged 4–18 years: 20 weeks of OMT. Effects of the OMT program will be evaluated on: sleep parameters (e.g., obstructive Apnea–Hyponea Index (oAHI), snoring frequency); orofacial functions (e.g., breathing pattern, tongue position at rest); quality of life outcomes. Methods: A pretest–posttest design will be used to evaluate the effectiveness of OMT in both children with and without Down syndrome and OSA. Both objective measures and patient-reported outcomes are being collected. Results: OMT is expected to improve orofacial functions, reduce OSA severity and symptoms, and enhance quality of life in both non-syndromic and syndromic children. Conclusions: This multidisciplinary research protocol, involving collaboration between ENT specialists and speech-language pathologists, aims to provide a comprehensive understanding of the potential benefits of OMT in treating OSA.